EFFECT OF DIETARY MEAL PLAN ON ANTHROPOMETRIC AND PHYSIOLOGICAL INDICES AMONG OVERWEIGHT WOMEN PRACTICING ZUMBA - Nurathirah Abd Mu’as; Normah Jusoh; Norhazira A Rahim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The aim of this study was to investigate the effects of dietary meal plan on anthropometric and physiological indices such as body weight, Body Mass Index (BMI), waist and hip circumferences, percentage of fat and blood pressure among overweight women practicing Zumba. The participants consisted of 20 overweight women who were aged 18 until 55 years old, which were not involved in weight loss program, not on medication, do not have any chronic diseases and did not consume any weight loss supplement or meal replacement. Body weight, BMI, waist circumference, hip circumference, percentage of fat and diastolic and systolic blood pressure were measured at the end week 1, week 4 and week 8. All participants received Zumba exercise along with dietary meal plan interventions and data were collected using a 24-hour dietary recall and a 3-days food diary. The effects of Zumba exercise with applied meal plan were analyzed by using one-way repeated measures MANOVA. The results showed that Zumba exercise combined with dietary meal plan showed a significant different in body weight (p<.001), BMI (p<.001), hip circumference (p<.001), waist circumference (p<.001), and percentage of fat (p<.001) after 8-week intervention. However, there was no significant difference in the systolic blood pressure (p<.05) after 8 weeks of intervention. Interestingly, these data show a significant difference between week 1 vs week 4 (p < .001) in this study. This study concludes that meal plan and Zumba exercise provide significant effects on body weight, BMI, hip and waist circumference, percentage of fat and systolic blood pressure (week 1 vs week 4) thus may improve anthropometric and physiological indices among overweight women.